Penerapan media big book untuk meningkatkan kemampuan membaca pemahaman siswa kelas III UPTD SD Inpres Oeba 2 Kupang - Yane Banamtuan; Labu Djuli; Rista A. Devi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research by Yane Banamtuan, Student ID 2201140029, titled “The Use of Big Books to Improve Reading Comprehension Skills Among Third-Grade Students at UPTD SD Inpres Oeba 2 Kupang.” This study investigates the research question: In what ways can large-format books enhance the reading comprehension abilities of third-grade pupils at UPTD SD Inpres Oeba 2 Kupang The goal of this research is to boost students' reading comprehension proficiency via large-format books. Multiple techniques were employed for gathering data, such as observation, testing, and documentation. The group involved in this study consisted of 21 students, comprising 7 male students and 14 female students. This study was conducted at the UPTD SD Inpres Oeba 2 Kupang, using the Classroom Action Research (CAR) approach, comprising two cycles. Each cycle featured phases of preparation, execution, observation, and evaluation. Findings indicated that during the initial pre-cycle stage, merely 8 students (38%) attained proficiency, whereas 13 students (62%) did not. Students’ reading comprehension skills began to improve after the big book medium was implemented. The results indicated that in Cycle I, only 7 students (33%) achieved mastery, while 14 students (67%) did not. Furthermore, in the second cycle, students’ reading comprehension skills improved more significantly. The research results showed that in Cycle II, 18 students (86%) achieved mastery, while 3 students (14%) did not. Students were more active, focused, and able to understand the content of the reading material well through the use of the engaging and interactive big book media. This study was conducted at the UPTD SD Inpres Oeba 2 Kupang employing a Classroom Action Research (CAR) method consisting of two cycles. Every cycle encompassed preparation, execution, monitoring, and evaluation. The research findings showed that before the cycle, only 8 students (38%) met the completion criteria, while 13 students (62%) were still below the standard.